Enhancing Customer Satisfaction In Food Trucks Through Service And Product Quality - Soerjanto; Ali Maksum (Institut Pariwisata dan Bisnis Internasional, 2025)
This study aims to analyze the impact of product and service quality on customer satisfaction in food trucks in the Jabodetabek area, Indonesia. The study uses a quantitative approach with multiple linear regression models. The sample is taken using a purposive sampling technique, which includes customers who have purchased food from food trucks at least twice. The study shows that both product and service quality positively and significantly affect customer satisfaction, both separately and simultaneously. These findings fill the research gap regarding the food truck industry in Indonesia. The study makes an important contribution for food truck entrepreneurs to improve quality to build customer loyalty, and also recommends further research that includes other factors such as price, location, and customer experience.